Evidence for periodic accretion–ejection in LS I +61°303. Issue 3 (27th August 2020) - Massi, M; Chernyakova, M; Kraus, A; Malyshev, D; Jaron, F; Kiehlmann, S; Dzib, S A; Sharma, R; Migliari, S; Readhead, A C S
ABSTRACT: The stellar binary system LS I +61°303, composed of a compact object in an eccentric orbit around a B0 Ve star, emits from radio up to γ-ray energies. The orbital modulation of radio spectral index, X-ray, and GeV γ-ray data suggests the presence of two peaks. This two-peaked profile is in line with the accretion theory predicting two accretion–ejection events for LS I +61°303 along the 26.5 d orbit. However, the existing multiwavelength data are not simultaneous. In this paper, we report the results of a campaign covering radio, X-ray, and γ-ray observations of the system along one single orbit. Our results confirm the two predicted events along the orbit and in addition show that the positions of radio and γ-ray peaks are coincident with X-ray dips as expected for radio and γ-ray emitting ejections depleting the X-ray emitting accretion flow. We discuss future observing strategies for a systematic study of the accretion–ejection physical processes in LS I +61°303.